2015
DOI: 10.1002/pbc.25823
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Neuroendocrine Tumors of the Appendix in Children and Adolescents: A Retrospective French Multicenter Study of 114 Cases

Abstract: Appendectomy alone seems to be curative of these tumors with no influence on life expectancy. Follow-up is not only unnecessary, but its means, whether clinical, radiological or biological, are ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
70
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 26 publications
10
70
0
4
Order By: Relevance
“…No survival advantage was therefore conferred by another procedure. This confirms the observations of several authors …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…No survival advantage was therefore conferred by another procedure. This confirms the observations of several authors …”
Section: Discussionsupporting
confidence: 93%
“…Several pediatric studies have questioned the use of these guidelines in children and the benefit of more extensive procedures like RHC following the incidental histological diagnosis of an appendiceal carcinoid …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ciarrocchi et al [25] utilised a propensity score model and showed that simple appendectomy was not inferior to RH regarding survival in patients with ANEN >2 cm. In the analysis of 114 cases of paediatric ANEN by de Lambert et al [26], 10 patients had tumours >2 cm and 20 patients had extension into the mesoappendix, including 5 with lympho-/vascular invasion. Ten of 29 cases with indications for hemicolectomy underwent further resection; however, no specimens demonstrated evidence of residual disease.…”
Section: Discussionmentioning
confidence: 99%